2008
DOI: 10.1016/j.ijrobp.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effects of Noscapine Enhance Radioresponse for GL261 Tumors

Abstract: Purpose-To determine whether the tubulin-binding drug noscapine could enhance radiosensitivity of GL261 glioma tumors by inhibiting tumor angiogenesis.Methods and Materials-The human T98G and murine GL261 glioma cell lines treated with noscapine, radiation, or both were assayed for clonogenic survival. Mice with established GL261 hind limb tumors were treated with noscapine, radiation or both to evaluate the effect of noscapine on radioresponse. In a separate experiment with the same treatment groups, 7 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Our results highlight the dire need to explore the underlying mechanisms of increasing DTX anticancer effect after Nos chemo-sensitization. Several studies have suggested that Nos induces multiple proapoptotic responses that induce apoptosis against variety of cancer cells [9,14,15,18]. Previously, our lab also reported the synergistic activity between Nos with cisplatin and gemcitabine in A549 and H460 lung cancer cells [9,19].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results highlight the dire need to explore the underlying mechanisms of increasing DTX anticancer effect after Nos chemo-sensitization. Several studies have suggested that Nos induces multiple proapoptotic responses that induce apoptosis against variety of cancer cells [9,14,15,18]. Previously, our lab also reported the synergistic activity between Nos with cisplatin and gemcitabine in A549 and H460 lung cancer cells [9,19].…”
Section: Discussionmentioning
confidence: 86%
“…Multiple investigations have shown that Nos acts though various mechanisms including its ability to inhibit microtubule assembly [12], suppress expression of hypoxia-inducible factor-1α [13], induce p21 and p53 [14], induce apoptosis-inducing factor (AIF) [15], activate c-Jun-N-terminal kinase (JNK) [16] and repress bcl-2 [10]. It has been reported that Nos can efficiently inhibit the growth of both paclitaxel-sensitive and paclitaxel-resistant ovarian cancer cells [16], suggesting that Nos may mediate anticancer effects though other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…17-AAG was studied in vitro and in vivo (established intracranial tumors) using GL261 murine model of glioma. It caused a G 2 phase arrest in glioma cells along with downregulation of cyclin B1 and statistically significant volume reduction in intracranial tumors when compared with controls [53]. The combination of gefitinib (tyrosine kinsase inhibitor targeting EGFR) with 17-AAG has shown a synergistic cytotoxic effect when exposed together to multiple glioma cell lines [54].…”
Section: Gliomamentioning
confidence: 99%
“…26 The GL261 glioma model has been characterized in depth by others and has been widely used to test experimental treatment strategies. [27][28][29][30][31][32] We recently published an extensive validation study on the use of in vivo bioluminescence (BLI) for the monitoring of DC immunotherapy in this model. 21 Since GL261 tumor cells are considered moderately immunogenic, they can be used for immunotherapeutic studies.…”
mentioning
confidence: 99%